Testing for fractional cointegration in subsamples by allowing for structural breaks - Tom Jannik Kreye (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2024)
In this paper, tests for fractional cointegration that allow for structural breaks in the long-run equilibrium are proposed. Traditional cointegration tests cannot handle shifts in fractional cointegration relationships, a limitation addressed here by allowing for a time-dependent memory parameter for the cointegration error. The tests are implemented by taking the extremum of a residual-based fractional cointegration test applied to different subsamples of the data. The subsampling procedures include sample splits, incremental samples, and rolling samples. A fairly general cointegration model is assumed, where the observed series and the cointegration error are fractionally integrated processes. Under the alternative hypothesis, the tests converge to the supremum of a chi-squared distribution. A Monte Carlo simulation is used to evaluate the finite sample performance of the tests.
Keywords: C12; C32; 330; Fractional Cointegration; Long Memory; Monte Carlo; Persistence Breaks; Structural Breaks; Subsample Analysis